CONTRIBUTION TO SAFETY OF NAVIGATION BY INTRODUCTION OF NEW TECHNOLOGIES IN FAIRWAY - Vidan, Pero; Vukša, Srđan; Gudelj, Anita; Čorić, Mirko (Journal of Applied Engineering Science, 2020)
Navigation in archipelagos and shallow waters is considered dangerous. Although islands, reefs, and shallows can be properly marked by lights and other navigation aids, skippers and other non-professional navigators usually do not have sufficient experience for safe navigation. Available navigation aids such as radars, Electronic Charts Display and Information System (ECDIS), and alike are usually expensive for use on small boats and pleasure crafts. In this paper, the authors propose a new system of identifying navigation marks that would significantly reduce the possibility of maritime accidents and errors due to a wrong interpretation or invisibility of the mark. The key part of the new system proposed refers to an innovative method that identifies, delivers, and displays in a user-friendly manner those navigation marks that are relevant to skippers and other non-professional navigators, depending on their location during navigation. The proposed system would be cheaper than the professional SOLAS-approved system, and available on the web.